Vertebral Body Osteolysis 6 Years After Cervical Disk Arthroplasty - Harati, Ali; Oni, Paul; Oles, Lucas; Reuter, Thomas; Hamdan, Mohammad (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Cervical arthroplasty is an accepted and widely performed surgical intervention with usually favorable outcomes. We report a rare case of a 37-year-old woman who presented with vertebral body osteolysis, 6 years after two-level cervical arthroplasty (C5–C6 and C6–C7). The patient showed no initial complications, but at year 6 she presented with neck and radicular arm pain. Diagnostic imaging revealed osteolysis of the vertebral body C6. The patient subsequently underwent removal of the two prostheses and C6 corpectomy, followed by bridging C5 to C7 and anterior fixation. During surgery, the mantle of the prostheses appeared broken, with the core expulsed anteriorly and embedded in granulomatous scar tissue. Pathologic evaluation of the samples showed partially proliferating fibroblasts, giant cell reaction, and textile particles. Postoperatively, clinical symptoms resolved with no residual deficits. Additional research should be performed to assess the long-term complications of this procedure that should be included in the patient informed consent materials.
Keywords: cervical arthroplasty; dynamic fixation; M6-C; vertebral body osteolysis; long-term complications